2013
DOI: 10.1038/jhh.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

Apparent treatment-resistant hypertension among elderly Korean hypertensives: an insight from the HIT registry

Abstract: The aim of this study was to determine the clinical characteristics of patients with resistant hypertension (RH) and predictors among elderly Korean hypertensives. This prospective, multi-center, observational study evaluated 2439 elderly hypertensive patients between December 2008 and November 2011, who visited secondary hypertension clinics for high blood pressure (BP). Patients were categorized as resistant if their BP was ≥140/90 mm Hg and if they reported using antihypertensive medications from three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Most studies reporting associations between CKD and aTRH have been cross-sectional [ 2 , 12 , 15 , 17 , 18 ] with one exception [ 19 ]. They have consistently showed a higher prevalence of aTRH associated with either lower estimated glomerular filtration rates (eGFR) or higher albumin-to-creatinine ratios (ACRs) or both, independent of other major determinants including age, gender, race, smoking, obesity, diabetes, and cardiovascular disease (CVD)[ 2 , 12 , 14 , 15 , 17 , 18 ]. The longitudinal association between the rate of kidney function decline and the risk of resistant hypertension, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reporting associations between CKD and aTRH have been cross-sectional [ 2 , 12 , 15 , 17 , 18 ] with one exception [ 19 ]. They have consistently showed a higher prevalence of aTRH associated with either lower estimated glomerular filtration rates (eGFR) or higher albumin-to-creatinine ratios (ACRs) or both, independent of other major determinants including age, gender, race, smoking, obesity, diabetes, and cardiovascular disease (CVD)[ 2 , 12 , 14 , 15 , 17 , 18 ]. The longitudinal association between the rate of kidney function decline and the risk of resistant hypertension, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal association between the rate of kidney function decline and the risk of resistant hypertension, however, is unknown. Moreover, although the risk of poor BP control increases greatly with age, few studies have focused on elderly populations [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study using the Korean population reported the prevalence of resistant hypertension as high as 7.9% in a primary care setting [ 14 ]. Choi et al [ 15 ] conducted a prospective multicenter observational study in the Korean elderly population (> 60 years old) who underwent evaluation of secondary hypertension and reported the prevalence of aTRH as 19.1%. In the most recent study using the Korean ambulatory blood pressure monitoring registry (Kor-ABP registry) data, Choi et al [ 16 ] reported that the prevalence of resistant hypertension was 11.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to the higher risk of RH in older adults [13,14]. They include age-related vascular changes (i.e., vascular stiffness), neurohormone imbalances, multiple comorbidities (including kidney disease, obesity, and diabetes), poor adherence to medication or polypharmacy, and insufficient lifestyle modifications (especially highsalt diets) [13,14]. Noubiap et al analyzed the prevalence of aTRH by region [11].…”
Section: Epidemiology Of Resistant Hypertensionmentioning
confidence: 99%